Subsidiary Learning Opportunities for the Sustainability of Early Child Development - Farzana Begum; Ambreen Nizar; Sidra Afzal (Journal of the Pakistan Medical Association, 2024)
Dear Sir / Madam In our fast-paced, ever-changing world, the key to a sustainable future is increasingly recognized as nurturing the potential of the youngest members of society.(1). New estimates are that 250 million children (43%) younger than 5 years in low-income and middle-income countries are at risk of not reaching their developmental potential (2). Early child development is the cornerstone upon which a sustainable future is built.(3) Subsidiary learning opportunities are found in the way a caregiver engages in conversation during mealtime, play, bedtime stories, and the wonder of discovering nature in a walk-through park.(4) Key Points Holistic Development: It fosters well-rounded children by encompassing cognitive, physical, social, and emotional development, ensuring they are academically proficient and possess crucial life skills like problem-solving, empathy, and resilience.(5). Early Exposure to Sustainability: this introduces children to sustainability, conservation, and responsible living through activities like gardening, recycling, and exploring nature, fostering an early appreciation for the environment. Cultural and Social Awareness: A global perspective fosters tolerance, understanding, and empathy towards different cultures and backgrounds. Parental Engagement: Subsidiary learning opportunities strengthen the bond to provide a stable, nurturing environment for their children’s growth, contributing to their overall development. Lifelong Learning: Children who are encouraged to explore and ask questions during these years are more likely to become curious, self-motivated learners throughout their lives. In conclusion, subsidiary learning opportunities are the unsung heroes of early child development, laying the groundwork for sustainable futures.